“Revitalización de las tradiciones y costumbres como aporte al desarrollo local de la Parroquia de Chugchilán del Cantón Sigchos”. - Toapanta Chicaiza, Evelyn Lilibeth (2023)
This research is focused on the revitalization of the traditions and customs of the parish Chugchilán, to obtain the desired results we proceeded with the realization of situational analysis of the parish, we used methods and techniques such as direct observation, use of inventory cards of the INPC where we were able to identify 3 oral expressions, 2 social uses, rituals and festive events, 2 in knowledge and uses related to nature and 1 in traditional craft techniques, In addition, we proceeded with the application of surveys where the information collected evidence the problem of the devaluation of the cultural manifestations of the communities, factors such as unemployment, migration and globalization have caused the new generations to move away from their cultural identity, having a different way of perceiving their behavior, leading to the loss of cultural heritage value. In the parish and the communities, research techniques such as the survey were used for the acceptance of the development of community tourism, where most people are willing to be part of the project by sharing their traditions and customs with tourists in addition to offering different activities such as adventure sports, gastronomy, lodging, among others, in order to achieve the momentum of community tourism and generate benefits that help improve their quality of life and maintain their cultural practices. It is proposed to work on the design of means of dissemination of oral expressions such as stories and legends that exist in the parish Chugchilán aimed at the younger population who are not familiar with the culture of the place and encourage the practice of cultural manifestations, the audiovisual material is recorded on a CD and on the YouTube platform for easy access, the material will also be delivered to the different educational institutions and the parish Gad who will be responsible for disseminating oral expressions.